Pemanfaatan Aplikasi Augmented Reality Untuk Pembelajaran Organ Tubuh Manusia Di Sekolah Dasar - Hernanda, Aldryan; Aji, Adam Sekti (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
The development of technology is now increasingly advanced, and growing rapidly. This development certainly has an influence on various sectors of human life, one of which is the education sector. The latest rapid technological development is the increasingly frequent use of devices, especially the use of smartphones in everyday life, including in the field of education. This opens up great opportunities in utilising application technology on smartphones to be developed into application-based learning media. One of them is to utilise Augmented Reality technology on android applications in science learning media for elementary school students so that learning becomes more effective and increases students' enthusiasm for learning. For this reason, Augmented Reality (AR) based learning media was developed with the Unity AR application of human organs for elementary school students, as well as seeing the quality of the resulting learning media in terms of validity, attractiveness, and practicality. The results of development research in the form of AR learning media show very good results and are suitable for use as learning media, both in class and independently.